2017
DOI: 10.1021/acs.biomac.7b01091
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition of Gentamicin-Loaded Silk Fibroin Coatings on 3D-Printed Porous Cobalt–Chromium–Molybdenum Bone Substitutes to Prevent Orthopedic Implant Infections

Abstract: In addition to customizing shapes of metal bone substitutes for patients, the 3D printing technique can reduce the modulus of the substitutes through the design and manufacture of interconnected porous structures, achieving the modulus match between substitute and surrounding bone to improve implant longevity. However, the porous bone substitutes take more risks of postoperative infection due to its much larger surface area compared with the traditional casting solid bone substitute. Here, we prepared of genta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…Both of these effects lead to finer crystallite structure and smaller size in the case of HAP/CS/Gr/Gent, which contributes to better osseointegration due to bone‐like apatite formation (Djošić, Mitrić, & Mišković‐Stankovic, 2015; Okada & Matsumoto, 2015). Namely, owing to their large surface‐to‐volume ratio HAP nanoparticles are considered to improve the in vitro bone‐like apatite formation, by increasing the specific area of biomaterial (Han et al, 2017; Zhang et al, 2018). Moreover, it was shown that a larger contact area enhanced the adhesive protein adsorption and thus contributed to the interactions between cells and biomaterial surfaces (Geuli et al, 2017; Thomas, Metoki, Mandler, & Eliaz, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Both of these effects lead to finer crystallite structure and smaller size in the case of HAP/CS/Gr/Gent, which contributes to better osseointegration due to bone‐like apatite formation (Djošić, Mitrić, & Mišković‐Stankovic, 2015; Okada & Matsumoto, 2015). Namely, owing to their large surface‐to‐volume ratio HAP nanoparticles are considered to improve the in vitro bone‐like apatite formation, by increasing the specific area of biomaterial (Han et al, 2017; Zhang et al, 2018). Moreover, it was shown that a larger contact area enhanced the adhesive protein adsorption and thus contributed to the interactions between cells and biomaterial surfaces (Geuli et al, 2017; Thomas, Metoki, Mandler, & Eliaz, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The topological design was found to be responsible for 10‐fold differences in mechanical properties, whereas the material type for up to twofold differences . While initial biological response to osteoblast‐like cells and the antibacterial properties of silk fibroin coatings have also been reported by the same authors, the current knowledge on the biological response and topographical effects of 3D‐printed CoCr lattices on osseointegration is still relatively poor.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, silk has also been widely used in flexible electronics, optical and photonic devices owing to the great flexibility and optical properties. Recent research also demonstrates that silk can be utilized for preservation of perishable products by coating them with an ultrathin silk film …”
Section: Introductionmentioning
confidence: 99%